Pengaruh Dosis Pupuk Ultradap Terhadap Pertumbuhan dan Produksi Tanaman Sawi Hijau (Brassica Juncea L.) - Ade Firman Syahru; Sugiyanto Sugiyanto; M. Husni (Fakultas Pertanian Universitas Borobudur, 2024)
This study aims to determine the effect of Ultradap fertilizer on the growth of green mustard plants (Brassica Juncea L). The research was conducted at the Dukuh Bima Housing Garden, Tambun Selatan Subdistrict, Bekasi Regency, from June to August 2022. The research employed a Monofactorial Design in a completely randomized design with a dosage experiment involving 4 levels: 0, 2, 4, and 6 g/L. The experiment was replicated 3 times with 3 sample plants established. The results of the study showed that the application of Ultradap fertilizer had a significant effect on the morphology (plant height, stem diameter, and root length) and physiology (growth biomass) of green mustard plants (Brassica Juncea L). The application of a 6 gr/L dose of Ultradap fertilizer yielded the best results for the following parameters: Plant height at 10-40 Days After Sowing (HST): 9.50 cm, 18.55 cm, 43.89 cm, and 50.44 cm. Stem diameter at 10 HST: 1.57 cm. Number of leaves at 10-40 HST: (5.11 leaves, 6.33 leaves, 10.78 leaves, and 12.89 leaves). Root length: (16.11 cm. Dry weight: 5.44 gr).